1989
DOI: 10.1007/bf01456548
|View full text |Cite
|
Sign up to set email alerts
|

Premature termination: A clinical study

Abstract: There have been many reasons posited for the phenomenon of premature termination in group psychotherapy. While there is no generally accepted definition of what constitutes "premature" termination, it generally refers to patients unilaterally deciding to leave their groups before their treatment goals have been achieved. Yalom (1985) presents a lengthy list of factors that can lead to such an outcome. Some of these factors are patient-specific, while others refer to problems that can exist within the group cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Adequate preparation is a theme that was highlighted by Yalom [28] and Bernard et al [29], and it could be argued that some of the barriers identified here could be easily overcome by adequate preparation. Factors such as providing sufficient information or accessible venues were seen to be key as to how successful a group was and are relatively easy to implement.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Adequate preparation is a theme that was highlighted by Yalom [28] and Bernard et al [29], and it could be argued that some of the barriers identified here could be easily overcome by adequate preparation. Factors such as providing sufficient information or accessible venues were seen to be key as to how successful a group was and are relatively easy to implement.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the idea of engaging in the group activities at will may be detrimental to the group process. Not all suggestions made by patients are actionable or even pragmatic within mental health services, and thus this reiterates the importance of having an overview of barriers and facilitators and categorising them in terms of ease of implementation, not just how preventable or unavoidable they are [29].…”
Section: Discussionmentioning
confidence: 99%
“…In group treatments, failure to express negative feelings is often attributable to the group's having developed norms that preclude such expression. 54 Therapists themselves may contribute to such norms by shifting focus away from patients whom they perceive as negative influences. 54 Therapists should actively encourage patients to express their doubts and questions about therapy.…”
Section: Facilitation Of Affect Expressionmentioning
confidence: 99%
“…54 Therapists themselves may contribute to such norms by shifting focus away from patients whom they perceive as negative influences. 54 Therapists should actively encourage patients to express their doubts and questions about therapy. Furthermore, therapists should permit patients to exhibit negative transference.…”
Section: Facilitation Of Affect Expressionmentioning
confidence: 99%
See 1 more Smart Citation